Using mixer efficiency testing to evaluate feed segregation in feed lines - C N Groesbeck; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
An experiment was conducted to evaluate potential diet segregation in feed lines by measuring coefficient of variation (CV) and mean salt concentration. The facility was a 1500-head gestation barn with nine feed lines, transected by a central feed line that conveyed feed from one of two bulk bins. QuantabÂ® chloride titrators were used to analyze the chloride concentration (salt) from samples collected at pre-determined feed line locations at various distances from the bulk bins. Thirty samples were collected from three feed lines (row 1, 5, and 9), ten samples were collected from drop boxes close to the central feed line (location 1), ten samples were collected from a central location within the row (location 2), and ten samples were collected from the furthest end of the feed line (location 3). Samples of approximately 50 g were collected directly from the feed drop. The sample collection procedure was repeated four times. After the first two sample collections, a bin agitator was added to the bulk bin. There was a feed line × distance (within the feed line) × agitator interaction (P>0.02) observed for CV. The addition of the bin agitator improved the CV in feed line 1 and 5, with no improvement observed in feed line 9. The CV observed before the addition of the agitator averaged 17.6, 18.6, and 14.3% for feed lines 1, 5, and 9, respectively, and the CV observed after the addition of the agitator averaged 13.6, 16, and 14% for feed line 1, 5, and 9 respectively. Within all feed lines (rows), distance CV was higher at locations 1 (17.3%) and 3 (17.6%), compared with CV at location 2 (15.6%) before the addition of the agitator, but was lower at locations 1 (14.3%) and 3 (13.0%), compared with CV at location 2 (15.6%) after the addition of the agitator. There was a mean-salt concentration effect (P<0.0001) observed for feed line. Feed lines 1 and 5 were similar in mean salt concentration, whereas feed line 9 consistently had the highest salt concentration. There was little to no feed segregation observed.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Feed segregation; Mixer efficiency; Pigs; Swine